Minat Belajar Santriwati Terhadap Pendidikan Pesantren Salaf di Pondok Pesantren Al-Is’af Kalabaan Guluk-Guluk Sumenep - Afifah Afifah; Zakiyatul Fahirah (Medan Resource Center, 2023)
Salaf Islamic boarding school education is a significant and intriguing institution in Islamic education. These traditional Islamic educational centers have deep historical roots in Indonesia, pre-dating the spread of public schools and madrassas into rural areas. This study addresses the interest of female students (santriwati) in Salaf pesantren education, which differs from modern general education. Salaf pesantren education remains rooted in tradition and lacks the typical graduation certificates found in mainstream schools. The research focuses on two key aspects: (1) the motivation of female students (santriwati) in pursuing Salaf pesantren education at Al-Is'af Kalabaan Guluk-Guluk Sumenep Islamic Boarding School; (2) the factors influencing the interest of students in Salaf pesantren education at Al-Is'af Islamic Boarding School Kalabaan Guluk-Guluk Sumenep. This qualitative study employs interviews, observations, and documentation as data collection methods. Findings suggest that female students' interest in Salaf pesantren education is driven by three primary factors: admiration for influential teachers, a desire to deepen religious knowledge, and an interest in learning the sciences of nahwu, fiqh, and women's fiqh. Furthermore, interest is influenced by internal factors like motivation and a love for the subjects, as well as external factors including caregiver motivation, teaching methods, parental support, and peer influence.